DNA methylation and mRNA expression of developmentally important genes in bovine oocytes collected from donors of different age categories. Issue 9 (20th September 2016) - Mattern, Felix; Herrmann, Doris; Heinzmann, Julia; Hadeler, Klaus Gerd; Bernal‐Ulloa, Sandra Milena; Haaf, Thomas; Niemann, Heiner
SUMMARY: Epigenetic changes are critical for the acquisition of developmental potential by oocytes and embryos, yet these changes may be sensitive to maternal ageing. Here, we investigated the impact of maternal ageing on DNA methylation and mRNA expression in a panel of eight genes that are critically involved in oocyte and embryo development. Bovine oocytes were collected from donors of three different age categories—prepubertal (9–12 months old), mature (3–7 years old), and aged (8–11 years old)—and were analyzed for gene‐specific DNA methylation ( bTERF2, bREC8, bBCL‐XL, bPISD, bBUB1, bDNMT3Lo, bH19, and bSNRPN ) and mRNA expression ( bTERF2, bBCL‐XL, bPISD, and bBUB1 ). A total of 1, 044 alleles with 88, 740 CpGs were amplified and sequenced from 362 bovine oocytes. Most of the detected molecules were either fully methylated or completely unmethylated. Only 9 out of 1, 044 alleles (<1%) were abnormally methylated (>50% of CpGs with an aberrant methylation status), and seven of the nine abnormally methylated alleles were within only two candidate genes ( bDNMT3Lo and bH19 ). No significant differences were detected with regard to mRNA expression between oocytes from the three groups of donors. These results suggest that genes predominantly important for early embryo development ( bH19 and bDNMT3Lo ) are less resistant to abnormal methylation than genes critically involved in oocyte development ( bTERF2, bBCL‐XL, bPISD, bBUB1, and bSNRPN ). Establishment of DNA methylation in bovine oocytes seems to be largely resistant to changes caused by maternal ageing, irrespective of whether the genes are critical to achieve developmental competence in oocytes or early embryos. Mol. Reprod. Dev. 83: 802–814, 2016 © 2016 Wiley Periodicals, Inc .